PEMBINAAN AKHLAK REMAJA BERBASIS KOMUNITAS SEBAGAI UPAYA PENCEGAHAN BULLYING DAN KENAKALAN REMAJA DI KELURAHAN BAJUBANG KABUPATEN BATANG HARI - Dinda Dwi Aryani; Intan Delia Saputri; Shella Ainun Sa’diyah; Sinta; Sukatin; Dinda Aulia (Yayasan Baitul Hikmah al-Zain, 2026)
Bullying behavior is an act that can take the form of violence or other negative actions, carried out repeatedly by an individual or group of people against someone who is powerless and unable to defend themselves. This bullying behavior can occur in various environments, such as in schools. Based on this, the background emerged that underlies the moral education seminar activities at SMA Negeri 5 Batang Hari. This activity was organized by students of the Universitas Islam Batanghari, and attended by students of SMA Negeri 5 Batang Hari. The activity was carried out face-to-face between the resource person and participants, where there was a presentation of material, discussion, and question and answer. The hope of holding this seminar is to increase the awareness of students about the importance of having good social interactions and morals towards others, as well as increasing anti-bullying towards others and social care.